Boost IORT in Breast Cancer: Body of Evidence. (2nd September 2014) - Sedlmayer, Felix; Reitsamer, Roland; Fussl, Christoph; Ziegler, Ingrid; Zehentmayr, Franz; Deutschmann, Heinz; Kopp, Peter; Fastner, Gerd
Abstract : The term IORT (intraoperative radiotherapy) is currently used for various techniques that show decisive differences in dose delivery. The largest evidence for boost IORT preceding whole breast irradiation (WBI) originates from intraoperative electron treatments with single doses around 10 Gy, providing outstandingly low local recurrence rates in any risk constellation also at long term analyses. Compared to other boost methods, an intraoperative treatment has evident advantages as follows. Precision. Direct visualisation of the tumour bed during surgery guarantees an accurate dose delivery. This fact has additionally gained importance in times of primary reconstruction techniques after lumpectomy to optimise cosmetic outcome. IORT is performed before breast tissue is mobilised for plastic purposes. Cosmesis. As a consequence of direct tissue exposure without distension by hematoma/seroma, IORT allows for small treatment volumes and complete skin sparing, both having a positive effect on late tissue tolerance and, hence, cosmetic appearance. Patient Comfort. Boost IORT marginally prolongs the surgical procedure, while significantly shortening postoperative radiotherapy. Its combination with a 3-week hypofractionated external beam radiotherapy to the whole breast (WBI) is presently tested in the HIOB trial (hypofractionated WBI preceded by IORT electron boost), a prospective multicenter trial of the International Society of Intraoperative Radiotherapy (ISIORT).